FACILITATIVE TECHNIQUES AS AN EFFECTIVE MEANS ADJUSTMENT OF GROUP DISCUSSION (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article reveals the practical effectiveness of facilitation. The main methods of the facilitator work are singled out. Facilitation mechanisms are proposed, which are focused on individual motivation, comfortable work in a group, providing the opportunity to express one's opinion, and improving approaches through discussion. The main tasks of the facilitator are defined and recommendations on intensification of group work are given. It is proved that the key to facilitating the communication process is the organization of space, attracting and promoting the potential of individual students and the group as a whole, as well as supporting participants in achieving their goals. The effectiveness of the transition to facilitative methods in order to effectively establish group discussion and increase the efficiency of any group on the way to achieving goals.
Keywords: facilitation, facilitative methods, group discussion, group work, communication, dialogue, discussion, comfortable space